2020
DOI: 10.1007/s00464-020-07766-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular complications after common bile duct stone extractions

Abstract: Background Common bile duct stone (CBDS) is a common condition the rate of which increases with age. Decision to treat in particular elderly and frail patients with CBDS is often complex and requires careful assessment of the risk for treatmentrelated cardiovascular complications. The aim of this study was to compare the rate of postoperative cardiovascular events in CBDS patients treated with the following: ERCP only; cholecystectomy only; cholecystectomy followed by delayed ERCP; cholecystectomy together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The other two patients had mortality secondary to sepsis after prolonged ICU hospitalization after perforation. In a nationally based study, it was reported that postoperative death occurred in 1.97% of 8,790 patients who underwent ERCP for choledocolithiasis [ 24 ]. These data suggest that our mortality data are at an acceptable rate.…”
Section: Discussionmentioning
confidence: 99%
“…The other two patients had mortality secondary to sepsis after prolonged ICU hospitalization after perforation. In a nationally based study, it was reported that postoperative death occurred in 1.97% of 8,790 patients who underwent ERCP for choledocolithiasis [ 24 ]. These data suggest that our mortality data are at an acceptable rate.…”
Section: Discussionmentioning
confidence: 99%
“…ERCP-ES and subsequent LC, the most preferred method worldwide[ 4 , 17 , 50 ], is a safe management process even in patients with cardiovascular disease[ 51 ]. A randomized controlled study showed that routine nasobiliary tubes after endoscopic CBD stone clearance can facilitate subsequent LC by the ability of the intraoperative cholangiography and ensure the anatomical integrity of the CBD[ 52 ].…”
Section: Managementmentioning
confidence: 99%
“…Sometimes the presence of small calculi was missed in preoperative examination, so that the surgeon did not carry out effective exploration of the common bile duct during the operation, resulting in residual common bile duct calculi. Common bile duct exploration should also not be performed too aggressively, as common bile duct exploration can lead to some of the more serious complications [ 13 ]. Therefore, the assessment and management of choledocholithiasis should be precise and cautious [ 14 ].…”
Section: Related Workmentioning
confidence: 99%